A new genus Carinopius gen. n. of the subfamily Opiinae (Hymenoptera, Braconidae) from China and Vietnam, with description of a new species - Tan, Jiang-Li; Tan, Qing-Qing; Achterberg, Cornelis Van; Chen, Xue-Xin (Zootaxa, 2016)
Carinopius gen. n. (type species: Carinopius albocoxalis Tan & van Achterberg, sp. n.) from China (Yunnan) and Vietnam is described and illustrated (Hymenoptera: Braconidae: Opiinae).